Wealth and Poverty ( Basics about their relationships ) - León González, Carlos (Revista Universidad de Guayaquil, 2015)
Biology, for your organization, set the starting point of the relationship that society assumes and recreates, as their own, to generate their perseverance in reality. Converge in making outsiders to provide food and reproductive objects that form the immortality of life, natural and social bodies. Diverge regarding the possession of objects in nature, constitute a material source of accumulation and individual differentiation, as it is in society. No differences in the take, if any relation to the magnitude of what you have. In nature, no one has more than he needs. In society itself; the result: very few have more than you need and many have fewer. The concepts of wealth and poverty are incubated in this matrix. Quantitatively, rich, it is who has more; poor, who owns less. Qualitatively, rich, it is who has the means to live for others, poor, is who can not afford to live on their own. Therefore wealth refers to making the foreign bodies and poverty deliver the bodies to demand others to survive. Extinguish qualitatively eliminate poverty is wealth; quantitatively disappear poverty does not seem to demand the death of wealth. Social understanding is on the quantitative. And this, for its natural sense, means growth redistribute or add little to add to what little chance the latest development of production seems to start to discard. The reason is obvious: there is no sustainable expansion in a finite world. The output of this quagmire exists as quality of life of indigenous peoples exist apart from generating relationships of poverty and wealth, have less and not want more than what is needed. At the end nature prevails and societies must be like her, what are at bottom.
Keywords: Society; nature; do; have; being; wealth; poverty; growth; limits; decrease